Perfectionism and dyadic relationship: a systematic review - Totonchi, Maryam; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2017)
The goal of this systematic review was summarized the existing evidence for the relationship between perfectionism and dyadic relationships find the best high-quality studies of perfectionism and dyadic relationships and identify a good and common instrument for evaluation perfectionism in dyadic. Two independent reviewers organized a systematic review of the literature by taking after Preferred Reporting Items for Systematic Review rules, and inclusion/exclusion criteria from 1995 to 2017. Databases: SCOPUS/ Web of Science/ Google Scholar/ Science Direct / SAGE. After review 2307 articles were recognized in the initial search, then 20 articles satisfied criteria for finish assessment. The result showed that a significant relationship between perfectionism and dyadic relationship.The majority of articles (n=13) had a moderate level of acceptance scoring 3 or 4of the 5 factors which were set by authors. Only three articles) got grade 5, they used all 5 factors evaluations. In this review two common and acceptable scales (MPS, APS-R) were identified.